The host galaxies of FeLoBAL quasars at z ∼ 0.9 are not dominated by recent major mergers. Issue 2 (30th November 2018) - Villforth, C; Herbst, H; Hamann, F; Hamilton, T; Bertemes, C; Efthymiadou, A; Hewlett, T
ABSTRACT: Theoretical models have suggested an evolutionary model for quasars, in which most of luminous quasars are triggered by major mergers. It is also postulated that reddening as well as powerful outflows indicate an early phase of activity, close to the merger event. We test this model on a sample of quasars with powerful low-ionization outflows seen in broad iron absorption lines (FeLoBAL). This sample of objects show strong reddening in the optical and fast (∼0.1c) high-column density outflows. We present HST WFC3/IR F160W imaging of 10 FeLoBAL host galaxies at redshifts z ∼ 0.9 (λ _ rest8500 A ). We compare the host galaxy morphologies and merger signatures of FeLoBALs to luminous blue non-BAL quasars from Villforth et al. (2017 ) of comparable luminosity, which show no excess of merger features compared to inactive control samples. If FeLoBAL quasars are indeed in a young evolutionary state, close in time to the initial merging event, they should have strong merger features. We find that the host galaxies of FeLoBAL quasars are of comparable luminosity to the host galaxies of optical quasars and show no enhanced merger rates. When looking only at quasars without strong point spread function residuals, an enhancement in disturbed and merger rates is seen. While FeLoBAL hosts show weak enhancements over a control of blue quasars, their host galaxies are not dominated by recent major mergers.